The in vitro free radical scavenging activity of tenidap, a new dual cyclo-oxygenase and 5-1ipoxygenase inhibitor - C. S. Lau; J. J. F. Belch (Hindawi Limited, 1992)
Tenidap, a new anti-inflammatory drug, is presently undergoing clinical studies as a treatment for rheumatoid arthritis (RA). Early pilot work has shown it to be of some benefit. Tenidap is a dual inhibitor of cyclo-oxygenase and 5-lipoxygenase enzymes. It has also been shown to modify white blood cell behaviour such as interleukin-1 production, monocyte differentiation and neutrophil degranulation. As free radicals (FRs) have been implicated in the pathogenesis of RA, we used an in vitro assay system developed by Misra and Fridovich to assess if tenidap has FR scavenging effects. Our study shows, for the first time, that tenidap has general FR scavenging effects although no effect on the superoxide anion (O2·-) could be demonstrated. This effect occurred in a dose-dependent manner at concentrations above 20 μg/ml (p < 0.005, Mann-Whitney U-test). As the therapeutic range of tenidap in serum is between 15 and 30 μg/ml such FR scavenging activity may be clinically relevant in the treatment of RA. Ex vivo confirmation of this possibility is underway.